TRADEMARKS MANAGEMENT: STRUGGLE AGAINST PARASITISM - Stepanenko, Sergiy (Journal of European Economy, 2017)
Essence and forms of ambush marketing as display of unethical competition and its effects on the authentic firm have been determined in the article. The author of the article has also defined directions of multipronged resistance to parasitism and has revealed its contents. Administrative-judicial and legal protection of trademark rights, which were outraged, have been proven in the article.